Investigation Of Surface Topology In Ball Nose End Milling Process Of Inconel 718 - Kasim, Mohd Shahir; Mohd Shahrim, Mohammad Shah All Hafiz; Ghani Abdul, Jaharah; Che Haron, Che Hassan; Raja Abdullah, Raja Izamshah; Sundi @ Suandi, Syahrul Azwan; Mohamed, Saiful Bahri; Othman, Intan Sharhida (Elsevier Ltd, 2019)
Inconel 718 known as hard-to-cut material due to its superior mechanical properties; high creep resistance, high fatigue strength, and able to withstand at elevated temperature which remains as challenge to possesses a lower surface roughness (Ra) during machining. The surface topology indicates the integrity of the machined parts. The quality of the Inconel 718 surface during end milling process was investigated. The experiments involved the use of PVD coated with TiAlN/ AlCrN ball nose tungsten carbide with varying of cutting speeds (Vc) ranging between 100 and 140 m/min, a feed rate (fz) of 0.1–0.2 mm/tooth, and an axial depth of cut (DoC) of 0.5–1.0 mm. The effects of the width of cut (WoC) between 0.2 and 1.8 mm were carried out. Due to the profile of the milled surface is complex; some variations in gap distance on the spiral profile were detected. The cutting path area to be found that, the new cut is overlapped which generate a new surface roughness by eliminating the previous cut thus the non-uniform feed marks being created on the machined surface. The surface roughness measured in feed direction was found to be lowered than pick a direction. Furthermore it was found that the WoC are causes the variation in Ra. During machining at low feed rates, the phenomenon of carbide particles was observed which results third body abrasion of machined surface. The particles are then trapped between the fragments and tear surface of the workpiece, thus increases the surface roughness. Based on the interaction effect of WoC and fz, it can be concluded that the feed rate effects on the quality of machined surface whilst WoC controls Ra variation.